Solvability for Discrete Fractional Boundary Value Problems with a p-Laplacian Operator - Weidong Lv (Discrete Dynamics in Nature and Society)
This paper is concerned with the solvability for a discrete fractional p-Laplacian boundary value problem. Some existence and uniqueness results are obtained by means of the Banach contraction mapping principle. Additionally, two representative examples are presented to illustrate the effectiveness of the main results.